Can we cure hepatitis B virus with novel direct‐acting antivirals?. (20th February 2020) - Martinez, Maria G.; Villeret, François; Testoni, Barbara; Zoulim, Fabien
Abstract: Current treatments against chronic hepatitis B (CHB) include pegylated interferon alpha (Peg‐IFNα) and nucleos(t)ide analogs (NAs), the latter targeting the viral retrotranscriptase, thus inhibiting de novo viral production. Although these therapies control infection and improve the patient's quality of life, they do not cure HBV‐infected hepatocytes. A complete HBV cure is currently not possible because of the presence of the stable DNA intermediate covalently closed circular DNA (cccDNA). Current efforts are focused on achieving a functional cure, defined by the loss of Hepatitis B surface antigen (HBsAg) and undetectable HBV DNA levels in serum, and on exploring novel targets and molecules that are in the pipeline for early clinical trials. The likelihood of achieving a long‐lasting functional cure, with no rebound after therapy cessation, is higher using combination therapies targeting different steps in the hepatitis B virus (HBV) replication cycle. Novel treatments and their combinations are discussed for their potential to cure HBV infection, as well as exciting new technologies that could directly target cccDNA and cure without killing the infected cells.